1993
DOI: 10.1177/001872089303500304
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Characteristics of Rapid Cursor-Positioning Movements with Electromechanical Mice in Human-Computer Interaction

Abstract: This research examines how people make movements with pointing devices during human-computer interaction. It specifically concerns the perceptual-motor processes that mediate the speed and accuracy of cursor positioning with electromechanical mice. In three experiments we investigated the spatial and temporal characteristics of positioning movements made with a mouse, analyzing subjects' speed and accuracy as a function of the types of targets that the movements had to reach. Experiment 1 required rapid and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 33 publications
8
53
0
Order By: Relevance
“…During the last few years, the use of computer mice to collect movement control data has increased (see, e.g., Baccino & Pynte, 1994;Walker, Meyer, & Smelcer, 1993). This is partly due to recent articles about the underlying structure of the data stream that researchers gather with computer mice and software (e.g., Crosbie, 1990).…”
Section: Most Current Movement Control Theories Include the Idea Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last few years, the use of computer mice to collect movement control data has increased (see, e.g., Baccino & Pynte, 1994;Walker, Meyer, & Smelcer, 1993). This is partly due to recent articles about the underlying structure of the data stream that researchers gather with computer mice and software (e.g., Crosbie, 1990).…”
Section: Most Current Movement Control Theories Include the Idea Thatmentioning
confidence: 99%
“…Changes may be needed if the mouse samples at a different rate or the pixel size is different, but we have found the program to be usable for data collected using different mouse drivers (two versions of Microsoft up to Version 9.01 and one version of Logitech drivers) and different sampling rates. In our previous work, we have primarily used a Microsoft bus allowing us to sample at 200 Hz (Walker et al, 1993), but we have also tested the parser program on data collected at lower sampling rates. The programs can be adjusted to allow different sampling rates to be used (as with the data from a serial port mouse).…”
Section: Model Of the Submovement Structure Of Mouse Movementmentioning
confidence: 99%
“…There has only been a limited application of kinematic techniques to address the underlying nature of cursor positioning movements using a restricted number of cursor control devices. Walker, Meyer and Smelcer (1993) examined the number of submovements required when a Mouse was used to move a cursor over different distances to rectangular targets of varying horizontal and vertical dimensions. Walker et al found the number of submovements increased when movements were made to targets requiring greater precision.…”
Section: Introductionmentioning
confidence: 99%
“…Since direction of motion has been observed to affect positioning time (Trankle & Deutschmann, 1991), we compared leftwards diagonal, vertical and rightwards diagonal movements. As geometrical factors have had an impact upon cursor positioning times (Walker et al, 1993), AJIS vol. 7, no 2 May 2000 circular targets were used to control target approach angle.…”
Section: Introductionmentioning
confidence: 99%
“…Timing and/or log information is used in many research areas, including evaluating the usability of different pointing devices (Kabbash, I. MacKenzie, & Buxton, 1993;S. MacKenzie, Sellen, & Buxton, 1991;Riviere & Thakor, 1996), the evaluation of keyboard designs (Smutz, Serina, & Rempel, 1994), investigating theories of human movement control (Gillan, Holden, Adam, Rudisill, & Magee, 1990;Walker, Meyer, & Smelcer, 1993), looking at individual differences in typing characteristics (Leggett, Williams, Usnick, & Longnecker, 1991), and evaluation of application programs and their interfaces (Brewster, Wright, & Edwards, 1994;Roberts & Moran, 1983).…”
mentioning
confidence: 99%